Research of sorptive processes of extraction of petroleum extraction from water by means of clay sorbents in static conditions - Kyrychenko, O. V.; Maliovanyi, M. S.; Sakalova, H. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Sorptive processes of water cleaning from oil pollution were investigated in this research. The sorption capacity of natural clay minerals and their modified forms in static conditions were characterized by means of the isotherm. It was determined that the process of water cleaning corresponds to the models of mixed diffusion model at nonlinear isotherm.